Vampire Island - Griffin, Adele (New York Scholastic, 2009)
Siblings Maddy, Lexie, and Hudson Livingstone, who are vampire-fruit bat hybrids, struggle to adjust to living as humans in New York City while maintaining their individual vampire strengths.
107138
Keywords: Vampires -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Neighbors -- Juvenile fiction; Schools -- Juvenile fiction; Environmental protection -- Juvenile fiction; New York (N.Y.) -- Juvenile fiction; New York (State) -- New York; Fiction; Juvenile works